DIGITAL DEXTERITY: STRATEGIC ENABLER YANG MENDORONG ORGANISASI MENUJU TRANSFORMASI DIGITAL - Asrunputri, Aisyah Pia; Scorita, Kurnia Budhy (Kinerja, 2022)
The purpose of this study was to determine respondents' perceptions regarding digital dexterity in the workplace. The research also focuses on how digital dexterity includes critical skills such as mobilize, execute, transform, and agility. This type of research is exploratory-descriptive using 20 items of the 8 elements of the digital dexterity instrument developed by Capgemini Consulting. The results show that there are still many organizations that do not fully have adequate access to adapt to the digital era or the industrial revolution 4.0. This also prevents employees from receiving the training, facilities and infrastructure needed. Therefore, access to adequate technology, training and digital skills development are needed for employees to be able to create human resources that are ready to face the digital transformation needed.